2022
DOI: 10.3390/polym14101960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Composition of Copolymers Based on Glycidyl Methacrylate and Fluoroalkyl Methacrylates on the Free Energy and Lyophilic Properties of the Modified Surface

Abstract: This study proposes to use reactive copolymers based on glycidyl methacrylate and fluoroalkyl methacrylates with a low fluorine content in the monomer unit as agents to reduce the surface free energy (SFE). This work reveals the effect of the structure and composition of copolymers on the SFE and water-repellent properties of these coatings. On a smooth surface, coatings based on copolymers of glycidyl methacrylate and fluoroalkyl methacrylates with fluorine atoms in the monomer unit ranging from three to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Klimov et al also developed self-cleaning coatings based on diblock copolymers of PGMA and PFMA with fluorine atoms in the monomer unit ranging from three to seven. They also found that by increasing the fluorine content in the copolymers, water repellency was enhanced …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Klimov et al also developed self-cleaning coatings based on diblock copolymers of PGMA and PFMA with fluorine atoms in the monomer unit ranging from three to seven. They also found that by increasing the fluorine content in the copolymers, water repellency was enhanced …”
Section: Introductionmentioning
confidence: 96%
“…They also found that by increasing the fluorine content in the copolymers, water repellency was enhanced. 52 To this end, P(GMA-co-FMA) copolymers have the capability to serve as water and oil repellent materials. To our knowledge, only a few articles have reported on grafting P(GMA-co-FMA) random copolymers onto surfaces to create hydrophobic/oleophobic nanocoatings.…”
Section: Introductionmentioning
confidence: 99%
“…GMA-based copolymers are of great importance in biotechnological applications since the epoxy group can be easily converted to other functional groups. In addition, homogeneous and heterogeneous polymer networks can be prepared with GMA used in coatings, matrix resins and adhesives (Wang et al, 2022;Liu et al, 2022;Waly et al, 2020;Klimow et al, 2022;Wang & Hutchinson, 2008;Muzammil et al, 2017;May, 1988;Matt et al,2021;Kovar et al, 1982;Yılmaz & Coşkun, 1982). Polyethylene glycol (PEG) is a straight or branched chain polymer in which oxygen and ethylene units are sequentially bonded to each other.…”
Section: Introductionmentioning
confidence: 99%